2018
DOI: 10.3389/fneur.2018.00287
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Information Transfer in Functional Corticomuscular Coupling Estimation Following Stroke: A Pilot Study

Abstract: Recently, functional corticomuscular coupling (FCMC) between the cortex and the contralateral muscle has been used to evaluate motor function after stroke. As we know, the motor-control system is a closed-loop system that is regulated by complex self-regulating and interactive mechanisms which operate in multiple spatial and temporal scales. Multiscale analysis can represent the inherent complexity. However, previous studies in FCMC for stroke patients mainly focused on the coupling strength in single-time sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Compared to the healthy controls, we did not observe significant directional differences in the strength of information flow both in the beta and gamma bands. This may be due to structural damage to the patient's brain, which affects normal information interaction [ 50 ]. Another possible explanation is that the individual differences among patients caused by factors such as different disease levels, different brain damage locations, and different stroke onset times.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the healthy controls, we did not observe significant directional differences in the strength of information flow both in the beta and gamma bands. This may be due to structural damage to the patient's brain, which affects normal information interaction [ 50 ]. Another possible explanation is that the individual differences among patients caused by factors such as different disease levels, different brain damage locations, and different stroke onset times.…”
Section: Discussionmentioning
confidence: 99%
“…The term multiscale TE analysis has been used before, but with a different meaning. In [22], [23], the authors employ a graining pre-processing operator that performs local averaging of considered signals. They propose averaging over windows of different lengths prior to the computation of TE and refer to the methodology as multiscale TE.…”
Section: B Multiscale Wavelet Transfer Entropymentioning
confidence: 99%
“…Information theory provides principled tools to quantify the transmission of information, such as mutual information (MI), directed information (DI), and transfer entropy (TE). Their model-free nature and ability to capture both linear and non-linear relationships has spurred considerable interest in their potential for detecting and quantifying functional neurophysiological coupling [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23]. Neurophysiological information transfer takes place within and across distinct functional bands of neural oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have reported the coupling/synchronization of alpha-band (8-14Hz) during static/isometric contractions, finger movements and the transition between force targets [6][7][8]. On the other hand, beta rhythm (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) coupling has been indicated as the main contributor to movement control [9,10]. Maximum beta rhythm coupling is observed during maintaining steady-state force and also controlling the fine motor control tasks [5,11].…”
Section: Introductionmentioning
confidence: 99%